(untitled) (Research, Society and Development, 2022)
Forest fires occur annually in the Pantanal Mato-grossense in periods of drought causing morbidit and mortality of numerous animal species, and the giant anteaters are among the main victims of these catastrophes. Due to the difficult breeding captivy of this specie, there are few data in the veterinary literature regarding the hematological and biochemical profiles of healthy giant anteaters and there is no description of the aletreations found in these animals with termal injuries caused by fire. Therefore, the objective was to evaluate the hematological and biochemical profiles of giant anteaters from areas on fire in the Pantanal (MT) in 2020, as well as to determine the most frequent laboratory alterations. In the Veterinary Clinical Pathology Laboratory of HOVET-UFMT, complete blood count and serum biochemistry of blood samples from six individuals of the specie Myrmecophaga tridactyla after hospital admission. Among the evaluated results, it was observed that: 83,3% (5/6) of the animals had hypochromic normocytic anemia on erythrograms, on white blood cell counts 66,7% (4/6) had left shift and neutropenia, in addition to other findings predominant in blood counts as total plasma hypoproteinemia observed in 100% (6/6) of individuals and thrombocytosis in 66,7% (4/6). Few changes were observed in serum biochemistry, unlike data found in human literature. It was concluded that giant anteaters with severe thermal burns show mainly laboratory alterations in the blood count and few biochemical alterations in a first post- rescue evaluation. Thus, stressing the need to perform these tests at various time intervals after injury to better understand the laboratory changes suffered by these patients, given that all individuals in this study died.